Elastography in pancreatic solid tumours diagnoses - Dyrla, Przemysław; Gil, Jerzy; Florek, Michał; Saracyn, Marek; Grala, Bartłomiej; Jędrzejewski, Emil; Wojtuń, Stanisław; Lubas, Arkadiusz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : Pancreatic solid tumour diagnoses remain a challenge for modern medicine. However, using endosonography together with elastography helps to examine the elasticity of tissues and therefore may allow definition of the nature of pancreatic tumours. Aim: To evaluate the usefulness of elastography with the strain ratio method and quantitative evaluation of pancreatic solid tumours. Material and methods : A total of 54 patients with pancreatic solid tumours were treated with ultrasound endosonography with fine-needle aspiration biopsy. The control group contained 26 patients with normal pancreas. Pancreatic solid tumours and normal pancreas were analysed with elastography and elasticity evaluation of the interest area (A), reference (B), and the strain ratio factor (B/A). Postoperative histopathological or cytological examinations were the final diagnoses. Both postoperative and cytological diagnoses were compared with average elasticity parameters (A) and strain ratio factors (B/A). Results: Average elasticity parameters (A) and the strain ratio factors (B/A) were: 0.025% (0.01–0.05%) for malignant process, and (B/A) 33.93 (18.23–75.45); (A) – 0.26% (0.14–0.35%), and (B/A) 5.35 (3.47–7.8) for inflammatory process; (A) 0.54% (0.35–0.82%), and (B/A) 1.79 (1.02–2.05) for normal pancreatic tissue. Conclusions : Malignant tumours have higher tightness factor compared to inflammatory tumours and normal pancreatic tissue. Elasticity parameters reach the highest levels in normal pancreatic tissue, lower in inflammatory tumours, and the lowest in malignant tumours.